2015
DOI: 10.4103/0189-6725.160368
|View full text |Cite
|
Sign up to set email alerts
|

Transient versus surgically managed small bowel intussusception in children: Role of ultrasound

Abstract: Background:To evaluate and compare the ultrasound (US) features of transient small bowel intussusception (SBI) with those which required surgical management.Materials and Methods:US features of 26 children with 32 intussusceptions from January 2014 to August 2014 were recorded and compared with follow-up imaging or surgical findings.Results:Transient SBI when compared to surgically managed intussusception has shorter length of intussusception (mean 2.25 cm, range 1.8-4.5 cm vs. mean 5.6 cm, range, 2.3-7.8 cm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Firstly, ultrasonography is a simple, convenient, repeatable and the most commonly used examination method for intussusception investigation with high sensitivity, and specificity. [ 19 ] Secondly, there is no risk of exposure to ionizing radiation and allergy to contrast material compared with computed tomography. Moreover, it is a noninvasive method and needs no special preparation compared with colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, ultrasonography is a simple, convenient, repeatable and the most commonly used examination method for intussusception investigation with high sensitivity, and specificity. [ 19 ] Secondly, there is no risk of exposure to ionizing radiation and allergy to contrast material compared with computed tomography. Moreover, it is a noninvasive method and needs no special preparation compared with colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…These include normal appearance of the bowel wall, normal wall thickness (<4 mm), short intussusception length (<3.5 cm), small intussusception diameter (<2.5 cm), normal blood flow characteristics on colour Doppler, lack of pain (in asymptomatic transient intussusception only), absence of a PLP, non-dilated proximal bowel, normal peristalsis, absence of ascites, progressive resolution of intussusception under real-time visualisation or on follow-up imaging, and benign clinical course with complete resolution of symptoms. 14,[21][22][23] However, like all intussusceptions, transient intussusceptions can also be caused by PLPs (Figure 7), the presence of adhesions or even the presence of intraluminal devices (Figure 8). To assist clinicians in managing patients with intussusception, sonographers should provide a detailed clinical ultrasound report containing as much detail as possible, including the location of intussusception, bowel segment involved, total diameter and length of intussusception, bowel wall thickness, associated oedema, signs of ischaemia, the presence of a lead point, the presence of free fluid, symptomatology under direct sonopalpation and the degree of diagnostic confidence based on the expertise of the sonographer and the radiologist.…”
Section: Imagingmentioning
confidence: 99%
“…24 It is important to note that only complete resolution of the intussusception and associated clinical signs can ultimately distinguish transient from persistent intussusception. 8,14 Transient symptomatic intussusception (TSI) Numerous authors have reported the spontaneous resolution of intussusception in children 5,9,14,[21][22][23] and adults. 8,10,12,13,[25][26][27][28][29][30] In some patients, resolution of symptoms may occur before any management decisions are made.…”
Section: Imagingmentioning
confidence: 99%
See 2 more Smart Citations